Child Exploitation of the Character Zain in the Film Capernaum by Nadine Labaki - Sindy Febrianisa; Muhammad Nazar; Fouad Larhzizer (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
Zain is the main character in the Capernaum movie directed by Nadine Labaki who described as having a love, devoted, kind, humane character, and not afraid of anything. Based on this, a contracted analysis was carried out on Zain. This research uses a qualitative approach with descriptive methods. The data in this study uses the words, sentences and contexts in this film that are related to Zain. The data source in this study uses a movie entitled "Capernaum" in 2018 directed by Nadine Labaki. The results of the study reveal that the results of the deconstruction analysis of exploitation experienced by Zein can occur in various forms, such as being forced to work or carrying out heavy life burdens, which should not be the responsibility of a child. Her parents used Zein for their personal interests, both financially and emotionally, without considering Zein's rights and welfare as an individual. of Zain who has the character of a stubborn, angry, deviant, and inhumane person, and there are also where his character is able to break speculation that men must be masculine, whereas after decontracting it can be found that Zain is also has a feminist character.